2007
DOI: 10.1007/s11325-007-0145-7
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity studies of the Turkish version of the Epworth Sleepiness Scale

Abstract: The Epworth Sleepiness Scale (ESS) is a self-administered eight-item questionnaire that is widely used in English speaking countries for assessment of daytime sleepiness in adults. The aim of this study was to investigate the reliability and validity of the ESS in the Turkish language. The Turkish version of the ESS (ESStr) was applied to 194 healthy controls and 150 consecutive subjects attending the sleep centre with symptoms of sleep-disordered breathing. Test-retest reliability of the ESStr was tested in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
1
24

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(201 citation statements)
references
References 25 publications
9
162
1
24
Order By: Relevance
“…For the 135 individuals assessed in the present study, the scores obtained on the ESS-BR showed internal consistency similar to that of translations validated elsewhere, (24)(25)(26)(27)(28) despite the cultural and language differences among the populations analyzed. Comparing the ESS-BR scores obtained in the present study with those obtained in studies applying the original ESS, we found the scores to be similar for the control and OSAHS groups.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…For the 135 individuals assessed in the present study, the scores obtained on the ESS-BR showed internal consistency similar to that of translations validated elsewhere, (24)(25)(26)(27)(28) despite the cultural and language differences among the populations analyzed. Comparing the ESS-BR scores obtained in the present study with those obtained in studies applying the original ESS, we found the scores to be similar for the control and OSAHS groups.…”
Section: Discussionsupporting
confidence: 77%
“…(25)(26)(27)(28) In one study, (19) the ESS scores were significantly higher for patients with severe OSAHS than for those with mild or moderate OSAHS (p < 0.001), although no statistically significant difference was found between the mild and moderate forms. Unlike other validation studies, the present study evaluated only individuals submitted to polysomnography, which enhanced the stringency of the selection of the groups.…”
Section: Discussionmentioning
confidence: 93%
“…The characteristics of the included studies are summarized in Table 1. The excluded studies 11,[16][17][18][19][20][22][23][24] and the reasons for their exclusion are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A validity and reliability analysis of the Turkish version was conducted by Pündük, Gür, and Ercan [18]. The Turkish version of the Epworth Sleepiness Scale was additionally used to determine sleep quality [19].…”
Section: Methodsmentioning
confidence: 99%